Sensors: Superabsorbing Metasurfaces with Hybrid Ag–Au Nanostructures for Surface‐Enhanced Raman Spectroscopy Sensing of Drugs and Chemicals (Small Methods 7/2018). Issue 7 (12th July 2018) - Gao, Jun; Zhang, Nan; Ji, Dengxin; Song, Haomin; Liu, Youhai; Zhou, Lyu; Sun, Zhi; Jornet, Josep M.; Thompson, Alexis C.; Collins, R. Lorraine; Song, Yun; Jiang, Suhua; et al.
Abstract : In article number1800045, Yun Song, Qiaoqiang Gan, and co‐workers report a simple, low‐cost, scalable, and lithography‐free method to manufacture three‐layered metal–dielectric–metal superabsorbing metasurfaces with hybrid Ag–Au nanostructures for surface‐enhanced Raman spectroscopy (SERS) sensing of drugs and chemicals. The superior nanogap features pave the way toward more affordable and quantitative sensing using SERS technology.